Phytochemistry of plants used in traditional medicine - Hostettmann K.;Marston, A.;Maillard, M.;Hamburger, M. (Oxford, United Kingdom : Claredon Press, 1995)
This volume is compilation of contributors from 16 speakers who presented plenary lectures at the International Symposium of the Phytochemical Society of Europe entitled "Phytochemistry of plants used in traditional medicine" held in Lausanne, Switzerland from 29 September to 1 October 1993.
Includes bibliographical references and index.